2017
DOI: 10.1007/s00392-017-1080-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated oscillometric blood pressure and pulse-wave acquisition for evaluation of vascular stiffness in atherosclerosis

Abstract: ObjectiveEvaluation of diagnostic accuracy of an oscillometry-based device (VascAssist) combining fully automated ankle-brachial index (ABI) and pulse-wave velocity (PWV) assessment for detection of peripheral arterial disease (PAD).Subjects and methods110 consecutive subjects including symptomatic PAD patients (n = 41) and healthy PAD-free participants (n = 69) were recruited. All subjects underwent standard manual Doppler-based ABI (sABI) and oscillometry-based automated ABI (aABI) measurements (VascAssist).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Another limitation is that baPWV was used instead of cfPWV, which is the gold standard. However, as several studies have demonstrated that baPWV and cfPWV are equally related to cardiovascular risk factors, we chose baPWV as a substitute [30,31]. In addition, urinary albumin excretion was measured from single-spot urine samples rather than 24-h urine samples in our study.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Another limitation is that baPWV was used instead of cfPWV, which is the gold standard. However, as several studies have demonstrated that baPWV and cfPWV are equally related to cardiovascular risk factors, we chose baPWV as a substitute [30,31]. In addition, urinary albumin excretion was measured from single-spot urine samples rather than 24-h urine samples in our study.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In this regard, baPWV appears to be a good alternative. It can be easily obtained by wrapping blood pressure cuffs on the extremities which is more convenient for patients and more easily to apply for technical staff [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in good agreement with theirs. On the other hand, Massmann 15 reported excellent correlation between the use of their automated oscillometric device and ABI determined by Doppler measurement, even in the subgroup of diabetic patients. However, they used ABI HABP for the comparison and they did not report the relationship between ABI values and actual PAD presence.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, oscillometric method using automated devices has been tested in numerous studies. The correlations between oscillometric ABI, Doppler ABI and actual PAD presence determined by colour duplex sonography or by angiography however vary greatly from excellent 14,15 through good results [16][17][18] to inconclusive or poor results 13,19,20 .…”
Section: Introductionmentioning
confidence: 99%